Acts of the General Assembly and Ordinances of the Trustees for the Organization and Government of the University of North Carolina 16 (1838) - (:unkn) unknown (My University, 1838)
Ch. 5, §§ 20-24: Every Student who shall send to any person a challenge or message, either in writing or otherwise, purporting to be a challenge to fight a duel, shall be expelled.
Keywords: DUELING